Regulating the use of shisha in Malaysia / Raja Yasmin Nadirah Raja Abdul Rahim, Tengku Aainaa Tengku Abdul Aziz and Nurazwa Abdul Rashid - Raja Abdul Rahim, Raja Yasmin Nadirah; Tengku Abdul Aziz, Tengku Aainaa; Abdul Rashid, Nurazwa (Faculty of Law, 2011)
From the literature review as well as the background of this research paper, it is apparent that the question on the challenges in regulating the use of shisha in Malaysia can be effectively addressed by carefully examining the strength and the weaknesses of law in Malaysia regarding this matter. It needs to be done in order to identify the gaps that need to be filled in which there is no specific legislation to regulate the use of shisha in Malaysia. Besides, there are a lot of other challenges that need to be faced by the Malaysian legislation in order to prosecute those smokers and retailers who misuse the use of shisha by selling it to underage kids and mixing shisha with illegal substances such as cannabis. Hence, the challenges in regulating the use of shisha in Malaysia can be overcome if Malaysia enacted a new law to explicitly include the definition of shisha and matters regarding shisha smoking in the Malaysian legislation.